The Role of BIM in Sustainable Construction Project Delivery Methods With Focus on Circular Economy - Sepehr Nourjalili; Fariborz Forouzannia (Engineering Reports)
ABSTRACT Delivery methods in sustainable construction projects and building information modeling (BIM) have addressed many problems and introduced many challenges and opportunities to improve the efficiency of construction project management. Using circular economy principles in construction provides an opportunity to improve environmental and economic indicators. This study examines the role of BIM in sustainable project delivery methods through circular economy principles. In this research, we studied the available literature to develop a questionnaire to measure the three variables including BIM, sustainable construction projects delivery methods and circular economy. In this paper, full‐time faculties and construction industry's experts were considered as the statistical population, whose number is equal to 210 people. Then, using Cochran's formula, the sample size was determined as 132 people. Afterwards, in order to collect data, 132 structured questionnaires were completed by building experts, who checked the importance of these factors. Moreover, the structural equation modeling approach has been used to investigate the relationship between research variables. The results showed that BIM has a positive and significant effect on sustainable project delivery methods, and about 50% of the total effect of BIM on sustainable project delivery methods is indirectly explained by the intermediate variable of circular economy.